Behavior of impurity elements in pure gadolinium during ultra-high purification. (April 2019) - Wang, Jiongkun; Fu, Kai; Li, Xingguo; Li, Guoling
Abstract: Deep purification, especially the removal of trace elements from the rare earth metal gadolinium (Gd) is challenging, due to their strong affinity and high chemical reactivity. Herein we present an effective approach to explore the purification mechanism via a novel Gas-solid two-phase method under high vacuum. All impurity elements were analyzed by glow discharge mass spectrometry (GDMS) and inert gas analysis (IGA). Both metallic impurities and oxygen can be reduced effectively after the purification process, especially the oxygen (O) concentration is close to zero. The chemical driving force, migration paths, migration laws and mechanisms of various impurity elements were studied in detail. Interactions of impurity elements during ultra-high purification process had been explored by using the specific technology of secondary ion mass spectroscopy (SIMS). Highlights: Ultra high purity rare earth gadolinium has been produced, moreover, residual oxygen content in Gd is close to zero. The key migration mechanisms of impurity elements can be attributed to the intrinsic vapor pressure properties and external chemical driving forces. AlCO alloy was discovered in the deoxidized Gd sample, proving the mutual pinning effect for ultra-high purification process.